2014
DOI: 10.1101/gr.176255.114
|View full text |Cite
|
Sign up to set email alerts
|

H3S28 phosphorylation is a hallmark of the transcriptional response to cellular stress

Abstract: The selectivity of transcriptional responses to extracellular cues is reflected by the deposition of stimulus-specific chromatin marks. Although histone H3 phosphorylation is a target of numerous signaling pathways, its role in transcriptional regulation remains poorly understood. Here, for the first time, we report a genome-wide analysis of H3S28 phosphorylation in a mammalian system in the context of stress signaling. We found that this mark targets as many as 50% of all stress-induced genes, underlining its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 72 publications
(92 reference statements)
2
44
1
Order By: Relevance
“…Whereas the published data suggest that H3S28 phosphorylation might be important for eviction of PcG components for derepression of PcG target genes upon stimulatory cues (Gehani et al, 2010;Lau and Cheung, 2011;Sawicka et al, 2014), our data reveal a so far unacknowledged function of the unphosphorylated state of H3S28. We show that serine 28 is required to enable proper methylation of H3K27 by PRC2 and thus to establish polycomb-dependent gene silencing.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Whereas the published data suggest that H3S28 phosphorylation might be important for eviction of PcG components for derepression of PcG target genes upon stimulatory cues (Gehani et al, 2010;Lau and Cheung, 2011;Sawicka et al, 2014), our data reveal a so far unacknowledged function of the unphosphorylated state of H3S28. We show that serine 28 is required to enable proper methylation of H3K27 by PRC2 and thus to establish polycomb-dependent gene silencing.…”
Section: Discussioncontrasting
confidence: 79%
“…Interphase H3S28ph has also been detected in mammals, where it was shown to counteract mammalian PRC1 and PRC2 chromatin binding. This mark derepresses PcG target genes in response to stress and developmental signaling (Gehani et al, 2010;Lau and Cheung, 2011) and activates stress response genes via displacement of HDAC corepressor complexes (Sawicka et al, 2014). However, biochemical studies showed that H3K27me3S28ph is refractory to demethylation by UTX (Sengoku and Yokoyama, 2011) and JMJD3 (Kruidenier et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Given the conserved role of MSKs in phosphorylation of H3S28 in other cell types (Drobic et al, 2010; Sawicka et al, 2014) and their broad expression profile, there is potential for the mechanisms and function that we describe here in macrophages to feature generally in p38/MAPK-dependent gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Kinases MSK1/2 were highlighted as integrators of both p38 and ERK signaling with the ability to phosphorylate histone H3 (Thomson, 1999). More recently, MSK1/2 activity and phosphorylation of either H3S10 or H3S28 has been linked to the transcription of immediate-early genes during the fibroblast stress-response (Drobic et al, 2010; Sawicka et al, 2014). Despite involvement in several biological processes, the functions and direct activity of histone phosphorylation are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, following UV exposure, the histone acetyltransferase p300 (also known as EP300) is recruited close to the MMP-1 promoter, regulating MMP-1 transcription by its catalytic activity (Kim et al, 2009). UV exposure induces phosphorylation of histone H3 serine 28 (H3S28p) at promoters of stress-response genes and causes dissociation of histone deacetylase (HDAC) co-repressor complexes that further accompanies enhanced levels of histone acetylation and transcriptional induction of these genes (Keum et al, 2013;Sawicka et al, 2014). H3S28 phosphorylation is furthermore involved in the regulation of RNA-polymerase-IIIdependent transcription (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%